2020
DOI: 10.1002/cam4.3375
|View full text |Cite
|
Sign up to set email alerts
|

Screening and bioinformatics analysis of a ceRNA network based on the circular RNAs, miRNAs, and mRNAs in pan‐cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…23 Advanced bioinformatic systems such as GEO and TCGA obtabases and several advantaged analytical methods have allowed researchers to obtain the specific gene expression patterns in different pathological conditions. 24 Here, our study reported that lncRNA GABPB1-AS1 competitively bound to miR-330 and derepressed ZNF367 expression, leading to activation of the cell cycle signaling pathway and the growth and metastasis of glioma cells.…”
Section: Discussionmentioning
confidence: 65%
“…23 Advanced bioinformatic systems such as GEO and TCGA obtabases and several advantaged analytical methods have allowed researchers to obtain the specific gene expression patterns in different pathological conditions. 24 Here, our study reported that lncRNA GABPB1-AS1 competitively bound to miR-330 and derepressed ZNF367 expression, leading to activation of the cell cycle signaling pathway and the growth and metastasis of glioma cells.…”
Section: Discussionmentioning
confidence: 65%
“…Recently, several studies have investigated circRNAs from a pan-cancer view but implemented different methods. Based on a circRNA-miRNA-mRNA network in pan-cancer, Chen et al discovered that the overexpression of hsa_circ_0004639 and down-regulation of hsa_circ_0008310 could decrease the malignancy of cancer cells which were supported by experimental evidence (25). Analyses of the pan-cancer dataset from the MiOncoCirc database associated CDR1as with angiogenesis, extracellular matrix organization, integrin binding, and collagen binding, as well as the composition of immune and stromal cells in the tumor microenvironment (26).…”
Section: Discussionmentioning
confidence: 98%
“…It has been pointed out that circRNAs can act as competing endogenous RNAs (ceRNAs) to competitively bind with targeted microRNAs (miRNAs), thereby influencing the function of miRNAs and their downstream mRNAs. 12 The ceRNA model implicated with circRNA, miRNA, and mRNA is frequently discussed in various cancers, including NPC. For instance, circCRIM1 has been found to bind with miR-422a and repress the inhibitory impact of miR-422a on FOXQ1, thus resulting in NPC metastasis and docetaxel chemoresistance.…”
Section: Introductionmentioning
confidence: 99%